2015
DOI: 10.1021/acs.jpcc.5b09503
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Luminescence Centers in Molecular-Sized Silicon Carbide Nanocrystals

Abstract: Understanding the fluorescence of complex systems such as small nanocrystals with various surface terminations in solution is still a scientific challenge. Here we show that the combination of advanced time-resolved spectroscopy and ab initio simulations, aided by surface engineering, is able to 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 43 publications
3
39
1
Order By: Relevance
“…The particles were then terminated with a variety of oxygen-containing species with a high concentration of carboxyl groups [33]. The preparation of the OH-terminated nanoparticles (SiC-OH) involved the reduction of SiC-x NPs via NaBH 4 in an aqueous solution [34]. The SiC-OH were then silanized for the preparation of the SiC-NH 2 particles.…”
Section: Nanoparticle Preparation and Characterizationmentioning
confidence: 99%
“…The particles were then terminated with a variety of oxygen-containing species with a high concentration of carboxyl groups [33]. The preparation of the OH-terminated nanoparticles (SiC-OH) involved the reduction of SiC-x NPs via NaBH 4 in an aqueous solution [34]. The SiC-OH were then silanized for the preparation of the SiC-NH 2 particles.…”
Section: Nanoparticle Preparation and Characterizationmentioning
confidence: 99%
“…Therefore, the SiC QDs can be used as stable light sources for sensors, cell imaging, and light‐emitting diodes . On the other hand, the surface of the SiC QD offers fruitful emission colors owing to existence of various surface defect‐related luminescence centers . For the SiC QDs with very small sizes, their surface defects play important roles in luminescence .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the surface of the SiC QD offers fruitful emission colors owing to existence of various surface defect‐related luminescence centers . For the SiC QDs with very small sizes, their surface defects play important roles in luminescence . The study had indicated that for the SiC QDs smaller than 1 nm, the surface defect‐related luminescence dominates .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations